Advances in Stable Isotope Monitoring of CO2 Under Elevated Pressures, Temperatures and Salinities: Selected Results from the Project CO2ISOLABEL - Barth, Johannes; Mader, Michael; Myrttinen, Anssi; Becker, Veith; van Geldern, Robert; Mayer, Bernhard (Geological Storage of CO2 – Long Term Security Aspects, 2015)

A new approach to quantify system efficiency with dissolved oxygen isotopes during engineered growth of Galdieria sulphuraria - Mader, Michael; Schwerna, Philipp; Buchholz, Rainer; van Geldern, Robert; Barth, Johannes (Algal Research, 2017)
The microalgae Galdieria sulphuraria was grown in a first technical approach in a closed system experiment for 29 days. In this time period, 6 separate flasks were sampled for oxygen concentration and their stable isotope ratios (O-18/O-16) in dissolved and headspace phases. The oxygen isotope composition of the water was also analysed as an input for the transfer of its O-18/O-16 ratio to molecular oxygen via production by algae. This photosynthetic transfer of the isotope composition of water was counterbalanced by oxygen consumption that enriched both phases in O-18. For this reason, neither dissolved oxygen nor oxygen in the headspace reached the O-18-depleted oxygen isotope ratio of H2O despite excessive photosynthesis. Oxygen that was produced by photosynthesis accumulated with a yield of 13.96 mmol L-1 in the headspace and with 0.5 mmol L-1 in the fluid phase. This difference was due to rapid degassing of the solution. It was further amplified by preferential consumption of the dissolved O-2 phase. In order to quantify oxygen production and its consumption we determined photosynthesis/respiration (P/R) ratios with a formula that combined O-2 concentrations and its isotope ratios. It revealed a P/R ratio of 7.7 after 11 days. After this it decreased again and moved towards dominance of respiration. With this work our results introduce a new method to monitor the growth and efficiency of algae in controlled experiments.
Keywords: Dissolved oxygen; Stable isotopes; Algae growth; Closed system; Respiration; Galdieria sulphuraria

Direct oxygen isotope effect identifies the rate-determining step of electrocatalytic OER at an oxidic surface - Haschke, Sandra; Mader, Michael; Schlicht, Stefanie; Roberts, André Michael; Angeles-Boza, Alfredo; Barth, Johannes; Bachmann, Julien (Nature Communications, 2018)
Understanding the mechanism of water oxidation to dioxygen represents the bottleneck towards the design of efficient energy storage schemes based on water splitting. The investigation of kinetic isotope effects has long been established for mechanistic studies of various such reactions. However, so far natural isotope abundance determination of O-2 produced at solid electrode surfaces has not been applied. Here, we demonstrate that such measurements are possible. Moreover, they are experimentally simple and sufficiently accurate to observe significant effects. Our measured kinetic isotope effects depend strongly on the electrode material and on the applied electrode potential. They suggest that in the case of iron oxide as the electrode material, the oxygen evolution reaction occurs via a rate-determining O-O bond formation via nucleophilic water attack on a ferryl unit.

Dissolved oxygen in water and its stable isotope effects: A review - Mader, Michael; Schmidt, Christian; van Geldern, Robert; Barth, Johannes (Chemical Geology, 2017)
Keywords: Aquatic chemistry; Dissolved oxygen; Fractionation; Stable isotopes; Water

Insights into agricultural influences and weathering processes from major ion patterns - van Geldern, Robert; Schulte, Peter; Mader, Michael; Baier, Alfons; Barth, Johannes; Juhlke, Tobias; Lee, Kern (Hydrological Processes, 2018)
Karst areas and their catchments pose a great challenge for protection because fast conduit flow results in low natural attenuation of anthropogenic contaminants. Studies of the hydrochemistry of karst sources and river solutes are an important tool for securing and managing water resources. A study of the geochemical downriver evolution of the Wiesent River and its tributaries, located in a typical karst terrain, revealed unexpected downstream decreases of nitrate with maximum mean values of 30mg/L at the source to minimum values of 18mg/L near the river mouth. This trend persisted over the length of the river even though increased agricultural activities are evident in the downstream section of the catchment. This pattern is caused by fertilizer inputs via diffusive and fast conduits flow from karst lithology in the upstream area that may have reached the river's source even from beyond the hydrological catchment boundaries. Further downstream, these influences became diluted by tributary inputs that drain subcatchments dominated by claystone and sandstone lithologies that increased potassium and sulphate concentrations. Our findings indicate that bedrock geology remains the dominant control on the major ion chemistry of the Wiesent River and that agricultural influences are strongest near the headwaters despite increased land use further downstream, due to long-term storage and accumulation in karst aquifers. This feature may not be unique to the Wiesent River system, as carbonates cover significant portions of the Earth's surface and subsequent work in other river systems could establish whether such patterns are ubiquitous worldwide.
Keywords: fertilizers; geochemistry; hydrology; karst; weathering; Wiesent River

River recharge versus O2 supply from the unsaturated zone in shallow riparian groundwater: A case study from the Selke River (Germany) - Mader, Michael; Roberts, André Michael; Porst, David; Schmidt, Christian; Trauth, Nico; van Geldern, Robert; Barth, Johannes (Science of the Total Environment, 2018)
Besides gas-water-exchange in surface waters, respiratory consumption of dissolved oxygen (DO) in adjacent riparian groundwater may trigger the addition of so far hardly explored sources from the unsaturated zone. These processes also systematically influence stable isotope ratios of DO and were investigated together with Cl− as a conservative tracer for water mixing in a near-river riparian groundwater system. The study focused on a losing stream section of the Selke River at the foot of the Harz Mountains (Germany). The study area exposed steep DO gradients between the stream water and riparian groundwater between April 2016 and May 2017. Our results indicated dominant influences of microbial community respiration with observed DO concentration gradients. These observations can be explained by DO from the river that is subject to fractionation by microbial respiration with a typical fractionation factor (αr) of 0.982. However, with such respiration dominance, we expected a simultaneous enrichment of δ18ODO towards values that are more positive than the well-known atmospheric O2 signal of +23.9‰ versus the Vienna Standard Mean Ocean Water standard (VSMOW). Surprisingly, our measurements revealed much lower δ18ODO values between +22‰ and +18‰ in the near-river groundwater. Mass balance calculations revealed that the DO pool in the shallow and unconfined aquifer receives contributions of up to about 80% by diffusion of oxygen from the vadose zone with a distinctly lower isotope value than the one of the atmosphere. This finding about additional oxygen sources from the unsaturated zone has numerous ramifications for oxygen related processes in near-river environments including the oxidation of pollutants, nutrients and ecosystem health.
Keywords: Riparian zone; Dissolved oxygen; Stable isotopes; Diffusion; Vadose zone

Spatial and temporal variations of pCO2, dissolved inorganic carbon, and stable isotopes along a temperate karstic watercourse - van Geldern, Robert; Schulte, Peter; Mader, Michael; Baier, Alfons; Barth, Johannes (Hydrological Processes, 2015)

Stable isotope mass balances versus concentration differences of dissolved inorganic carbon – implications for tracing carbon turnover in reservoirs - Barth, Johannes; Mader, Michael; Nenning, Franziska; van Geldern, Robert; Friese, Kurt (Isotopes in Environmental and Health Studies, 2017)